2021
DOI: 10.3389/fmolb.2021.721990
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Characterization Reveals ILF2 and ILF3 Affected Metabolic Adaptions in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal cancer (EC) is a common malignant disease in eastern countries. However, a study of the metabolomic characteristics associated with other biological factors in esophageal squamous cell carcinoma (ESCC) is limited. Interleukin enhancer binding factor 2 (ILF2) and ILF3, double-stranded RNA-binding proteins, have been reported to contribute to the occurrence and development of various types of malignancy. Nevertheless, the underlying functions of ILF2 and ILF3 in ESCC metabolic reprogramming have never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Metabolites that we found to differentiate pancreatic tumors were additionally noted in PubMed database to be linked with other gastrointestinal malignancies: esophageal [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ], stomach/gastric (GC) [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], liver/ hepatocellular carcinoma (HCC) [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and colon/colorectal (CRC) [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] ( Supplement Table S2 ). We noticed that there is still limited knowledge concerning metabolism disturbances linked to creatine and phosphatidylcholine, especially C2 and PC 34.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites that we found to differentiate pancreatic tumors were additionally noted in PubMed database to be linked with other gastrointestinal malignancies: esophageal [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ], stomach/gastric (GC) [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], liver/ hepatocellular carcinoma (HCC) [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and colon/colorectal (CRC) [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ] ( Supplement Table S2 ). We noticed that there is still limited knowledge concerning metabolism disturbances linked to creatine and phosphatidylcholine, especially C2 and PC 34.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, through the STRING, there is PPI between HNRNPR and PTBP1, RBMX and ILF2 in addition to proteins from the same family. Among these, ILF2 [ 41 ] has been shown to affect the metabolic adaptation of ESCC. PPI is also one of the factors promoting the formation of stress granules mentioned previously.…”
Section: Discussionmentioning
confidence: 99%
“…ILF3 has been reported to contribute to the development of various cancers ( Hu et al, 2013 ; Cheng et al, 2018 ; Liu et al, 2019 ). High expression of ILF3 was shown to be involved in the metabolic alterations in ESCC patients, especially for the intermediate metabolites of the glycolysis pathway ( Zang et al, 2021 ). Through survival analysis, we found that the expression of PSMD6 , RABEP2 , GRN , and STC2 were related to a poor ESCC prognosis, while the expression of ITCH , ILF3 , and PSMC4 were related to a good prognosis.…”
Section: Discussionmentioning
confidence: 99%